Actualization of Muhammad Natsir’s Islamic Educational Ideas the Transformation of Learning at Pesantren Persatuan Islam (PERSIS) - Imani, Insani Nurul; Syahidin, Syahidin; Surahman, Cucu (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to examine the actualization of Mohammad Natsir’s Islamic education ideas in the transformation of learning at Pesantren Persatuan Islam (Persis), specifically at PPI 1 Pajagalan located in Bandung City and PPI 31 Banjaran in Bandung Regency. The research method used is descriptive qualitative with a literature and case study approach. This research uses primary and secondary data. Primary data were obtained through a literature review of Natsir's works, as well as through interviews with curriculum managers and santri (student’s), direct observation of the learning process, and documentation of learning activities in both pesantren. Meanwhile, secondary data include scientific journals, books, and articles relevant to the research topic. Data analysis techniques used the Miles and Huberman model, as well as source and technique triangulation to maintain data validity. The results show that Mohammad Natsir's Islamic education ideas are well actualized in PPI 1 Pajagalan through a curriculum that integrates the values of tawhid, worship, science, and skills. Meanwhile, at PPI 31 Banjaran, although it does not explicitly refer to Natsir, the values that align with his thoughts are applied in the transformation of learning, especially in strengthening character and scientific integration. In conclusion, Natsir's educational thought is reflected in the learning system in both pesantren through a balanced combination of spiritual, intellectual, and practical aspects, in line with the principles of holistic Islamic education.